Women and photography - Taan, Yasmine Nachabe (2016)
This special issue of al-Raida on Women and Photography addresses photography as a medium that challenges gender roles, positions, and attributes as seen in the mainstream media. It includes papers by contributors who examine the practice of women photographers in the Middle East as well as the different ways women are represented in photographs.